PENGARUH TINGKAT KESEHATAN KEUANGAN BANK MENGGUNAKAN RGEC TERHADAP PERTUMBUHAN LABA: PENGARUH TINGKAT KESEHATAN KEUANGAN BANK MENGGUNAKAN RGEC TERHADAP PERTUMBUHAN LABA - Devi Allisya Putri; Willy Sri Yuliandhari (Universitas Widyatama, 2020)
Profit growth is very important for the company, because the company's performance can be seen from the growth in the company's profits. The research objective was to determine the effect of NPL, LDR, GCG, NIM, and CAR simultaneously and partially on profit growth in banking companies in the 2016-2018 Infobank15 index. This research is motivated by the growth of banking profit in Indonesia which has decreased in 2016, where profit is very important for the company. The research was conducted using quantitative methods with descriptive research type and hypothesis testing. The results of the Eviews 10 output show that the NPL, LDR, GCG, NIM, and CAR variables simultaneously influence profit growth. Partially the NPL variable has a negative effect on profit growth and the NIM variable has a positive effect on profit growth. Meanwhile, the LDR, GCG, and CAR variables have no effect on profit growth.